1996
DOI: 10.1021/bi9605503
|View full text |Cite
|
Sign up to set email alerts
|

Global Mapping of Structural Solutions Provided by the Extended X-ray Absorption Fine Structure ab Initio Code FEFF 6.01:  Structure of the Cryogenic Photoproduct of the Myoglobin−Carbon Monoxide Complex

Abstract: X-ray methods based on synchrotron technology have the promise of providing time-resolved structural data based on the high flux and brightness of the X-ray beams. One of the most closely examined problems in this area of time-resolved structure determination has been the examination of intermediates in ligand binding to myoglobin. Recent crystallographic experiments using synchrotron radiation have identified the protein tertiary and heme structural changes that occur upon photolysis of the myoglobin--carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 60 publications
7
36
0
Order By: Relevance
“…In all cases, the CO appears to be oriented with the C-O bond axis pointing toward the heme iron. A recent cryogenic EXAFS study of photolyzed MbCO [30] was found to be most consistent with the structure presented in Schlichting et al [17].…”
Section: Co Orientation In Mb7cosupporting
confidence: 81%
“…In all cases, the CO appears to be oriented with the C-O bond axis pointing toward the heme iron. A recent cryogenic EXAFS study of photolyzed MbCO [30] was found to be most consistent with the structure presented in Schlichting et al [17].…”
Section: Co Orientation In Mb7cosupporting
confidence: 81%
“…The beamline configuration is similar to that used for focused beam X-ray absorption spectroscopy measurements (Chance et al 1996), with the monochromator set to 10 keV, and harmonic rejection using a Ni-coated mirror. The setup consists of a multiplate rail positioned at 45°with respect to the beam that brings a sample plate in a position close to the synchrotron X-ray source, an x-z stage and two ionization chambers placed before and after the sample plate for precise alignment of a sample in the plate to the beam, and a multi-element, fast count rate, highresolution Germanium detector placed perpendicular to the beam path, that captures the X-ray fluorescence.…”
Section: Methods Metallomics Analysismentioning
confidence: 99%
“…The slightly lower edge energy of O 2 -␣Hb⅐AHSP compared with free O 2 -␣Hb suggests a lengthening of the Fe-O 2 bond in the AHSP complex. EXAFS data obtained from O 2 -␣Hb and O 2 -␣Hb⅐AHSP were fitted to models for the iron sites using restrained and constrained multiple-scattering models (58,(63)(64)(65). The observed and calculated EXAFS and the corresponding Fourier transforms are shown for O 2 -␣Hb and O 2 -␣Hb⅐AHSP in Fig.…”
Section: Comparison Of the Iron-ligand Structures In O 2 -␣Hb And O 2mentioning
confidence: 99%